Integrating Digital Technologies in Teaching Pencil Drawing in Higher Pedagogical Education - Sa’diyev Soli Tolipovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article examines the integration of digital technologies in teaching pencil drawing in higher pedagogical education. It explores how the use of graphic tablets, software applications, and online resources enhances students’ technical skills, creativity, and professional competencies. The study highlights the effectiveness of combining traditional pencil drawing techniques with modern digital tools, as well as the role of interactive teaching methods in fostering independent learning and aesthetic development.